Hypoxia response in Arabidopsis roots infected by Plasmodiophora brassicae supports the development of clubroot - Gravot, Antoine; Richard, Gautier; Lime, Tanguy; Lemarié, Séverine; Jubault, Mélanie; Lariagon, Christine; Lemoine, Jocelyne; Vicente, Jorge; Robert-Seilaniantz, Alexandre; Holdsworth, Michael J.; Manzanares-Dauleux, Maria J. (BioMed Central, 2016)
Background